Characteristics of National Competency Standards of Hospital Nursing Departments: An Analytic Hierarchy Process and Multidimensional Scale Analysis - Seon‐Nyeo Kim; Sue‐Kyung Sohn (Nursing Open)
ABSTRACT Aim This study was conducted to analyse national competency indicators of nursing departments, understand each department's competency characteristics and utilise them to assign departments and impart required education for nurses. Design This was a cross‐section study. Methods The national competency indicators were derived by analytic hierarchy process, based on 176 experienced nurses at general hospitals in Korea. These competency indicators were evaluated by multidimensional scale analysis to produce a perception map of nursing departments and understand their competency characteristics. The SQUIRE checklist was used to report the present study. Results The competency indicators of the wards were similar to the overall average. Regarding operating rooms, the competency indicators related to self‐management and the ability to understand documents were high. Regarding emergency rooms, the competency indicators related to problem‐solving and technical ability were high. Regarding the perception map centering around the ward, the position of each nursing department was different. Patient or Public Contribution No Patient or Public Contribution.